SEASONAL FLUCTUATION OF ROTIFERS AND CLADOCERAN IN HIGH ALTITUDE PND SARKOOT LOCATED IN DISTRICT KISHTWAR OF JAMMU AND KASHMIR - AKHTAR, ROMANA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Rotifers and Cladocerans form an important component of zooplanktonic community and are a natural resource of food for higher organisms, including fishes. They inhabit diverse habitats. In the present study fourteen species of rotifers and few species of cladocerans were recorded from theSarkoot pond located at Kishtwar in Doda district of Jammu and Kashmir state.